Desain Sitem Edukasi Rumah Baca Berbasis Resource Sharing Dengan Model Web Based Learning Di Desa Lau Gumba Kabupaten Karo - Zulham Sitorus; Eko Hariyanto; Fahmi Kurniawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
In improving the quality of people in Lau Gumba Village, Karo District as one of the tourist destinations in North Sumatra, a deeper review of the education of the Reading House in Lau Gumba Village is needed, so that the impact of the educational results can increase the ability of the community in reading interests in Lau Gumba Village especially in Alkaromah SMK School, Karo District. To support this read interest program requires Design and analysis based on Resource Sharing by taking the Web Based Learning approach as an educational model using web applications. The Reading House to be designed will later become a facility for the community, students and children who are in the village area. The Reading House in Lau Gumba Village is now used as a place of recreation, a place of discussion, socializing and counseling for the surrounding community. Utilization of Reading Houses that have not represented the functions of village libraries are caused by the limited quantity and quality of books that are collections, the lack of educational toys and the absence of volunteer teacher learning companions for the community and children in Lau Gumba Village. The aim of this research is to increase public reading interest in reading houses in Lau Gumba Village as education and information based on Resource Sharing with the Web Based Learning model